Schemes of approximation of linear systems with delay and analysis of their stability - Cherevko, Ihor (Чернівецький національний університет, 2023)
This paper investigates the application of approximation schemes for differential-difference equations to construct algorithms for the approximate finding of nonsymptotic roots of quasipolynomials and their application to study the stability of solutions of systems of linear differential equations with many delays
Keywords: differential-difference equations, approximation schemes, stability and asymptotic stability